Pathogenicity of Entomopathogenic Fungi on the Weevil of the Andes (Premnotrypes vorax Hustache) of the Potato (Solanum tuberosum L.) in Chimborazo Province, Ecuador - Erazo Sandoval N. S.; Lindao Córdova V. A.; Echeverría Guadalupe M. M.; Manzano Ocaña J. C.; Inca Chunata N. M. (European Scientific Journal, ESJ, 2018)
From thirty native isolates of entomopathogenic fungi, which were obtained from corpses of larvae and adults of Andean weevil (Premnotrypes vorax Hustache); two fungi with entomopathogenic characteristics were selected through laboratory tests, which will be used in a program of integrated management of this pest in the Ecuadorian inter-Andean region. The pathogenicity of the 30 isolates was determined by the mortality that they caused in larvae and adults and it was expressed in percentage; for this, a complete randomized design (CRD) was used. The LC50 and TL50 were determined by Probit analysis. The two selected isolates corresponded to: Metarhizium anisopliae (Metschnikoff 1879) Sorokin 1883 (A13) and  Beauveria bassiana (Bals.-Criv.) Vuill. 1912 (A21), which proved to be the best, because they caused the highest mortality in larvae of the fourth instar and adults of P. vorax. The Probit analysis showed that LC50 for A21 isolate (B. bassiana) in fourth instar larvae was obtained with a concentration of 1,75x109 spores/ml and 1,08x109 spores/ml for adults. Instead for A13 isolate (M. anisopliae), the LC50 was obtained with a concentration of 1,65x109 spores/ml for larvae and 2,42x109 spores/ml for adults. The LT50 for the selected isolates at the indicated concentrations, was 4,84 and 4,32 days for larvae with A13 and A21 isolates respectively, while, for adults, the shortest time was obtained with A21 isolate in 4.36 days, compared with A13 isolate, that delayed 20,70 days. The larval stage of P. vorax was the most susceptible to A13 isolate, on the other hand, larvae and adults were equally susceptible to A21 isolate at the indicated concentrations. According to the results obtained, the two selected isolates can be used as an alternative to the use of conventional agrochemicals, which will contribute to a more ecological production.